2017
DOI: 10.1515/cclm-2016-0572
|View full text |Cite
|
Sign up to set email alerts
|

Utility of proGRP as a tumor marker in the medullary thyroid carcinoma

Abstract: Background:Medullary thyroid carcinoma (MTC) is a neuroendocrine tumor caused by a malignant transformation in the parafollicular C-cells of the thyroid, where calcitonin (CT) is released. Nowadays the main tumor markers (TM) used in the diagnosis and follow-up of MTC patients are CT and carcinoembryonic antigen (CEA). Nonetheless, progastrin releasing peptide (proGRP) has been recently proposed as a TM useful in the MTC. Our aims were to investigate the release of proGRP in thyroid tumors, its role in the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Other secretory biomarkers as CEA, chromogranin A (CgA) and pro gastrin-releasing peptide (proGRP) increase at MTC and might be useful tumor markers, although CgA first increase in aggressive MTC (176)(177)(178)(179)(180). CEA is an integral part of the cell membrane of MTC tumor cells, from where it can be released and serve as a tumor marker (149,181).…”
Section: Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Other secretory biomarkers as CEA, chromogranin A (CgA) and pro gastrin-releasing peptide (proGRP) increase at MTC and might be useful tumor markers, although CgA first increase in aggressive MTC (176)(177)(178)(179)(180). CEA is an integral part of the cell membrane of MTC tumor cells, from where it can be released and serve as a tumor marker (149,181).…”
Section: Biochemistrymentioning
confidence: 99%
“…In contrast to serum calcitonin, which has to be analyzed immediately or transported frozen to the laboratory, proGRP is stable in blood where it can be measured (183,184). The ProGRP serum level may also be useful, in addition to calcitonin, in diagnosing and follow-up of MTC, and can be analyzed in FNB wash out (179,180 (189,190).…”
Section: Biochemistrymentioning
confidence: 99%
“…Regarding proGRP, it was widely distributed in neuroendocrine cells of non-gastric antrum, nerve bers, brain and lung [10,12]. Accumulating evidence suggested that proGRP levels also had signi cant correlation with MTC but not with non-MTC (follicular thyroid carcinoma [FTC] and papillary thyroid carcinoma [PTC]) [10,11,13]. Ide et al [10] reported that proGRP levels above the cut-off value, respectively, accounted for 80% ( [11] analyzed the sensitivity of Ctn, CEA and proGRP, individually and in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested that proGRP levels also had signi cant correlation with MTC but not with non-MTC (follicular thyroid carcinoma [FTC] and papillary thyroid carcinoma [PTC]) [10,11,13]. Ide et al [10] reported that proGRP levels above the cut-off value, respectively, accounted for 80% ( [11] analyzed the sensitivity of Ctn, CEA and proGRP, individually and in combination. The results showed: (i) Similar to Ctn (88.9%), sensitivity related predominance in terms of proGRP was observed as indicated by the CEA-to-proGRP ratio of approximately 1:1.4 (62.5%:88.9%); (ii) If CEA or proGRP is intended to be served as a complement to Ctn, respectively, the ratio of sensitivity was approximately 1:1.12 (88.9%:100%).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with residual, metastatic, progressive disease, classical cytotoxic drugs were proven to be inefficient. Drugs that inhibit different kinases, including RET, such as sorafenib, sunitinib, motesanib, cabozantinib and vandetanib, appear to be a key therapy for these patients (11).…”
mentioning
confidence: 99%